Pengaruh Bauran Pemasaran terhadap Kepuasan Konsumen di Coffee shop Asimetri Kopi Kabupaten Bogor: The Effect of Marketing Mix on Customer Satisfaction at Coffee shop Asimetri Kopi Bogor Regency - Najeela Zulaikha; Sulandjari, Kuswarini; Wicaksana, Indrajit (Universitas Pekalongan, 2025)
Asimetri Kopi is one of the coffee shops in Bogor Regency that sells a variety of food and beverage menus. Asimetri Kopi is experiencing several problems, one of which is low customer loyalty. The purpose of this study was to analyse the effect of the marketing mix consisting of product, price, place, promotion, process, people, and physical evidence both simultaneously and partially on customer satisfaction at Coffee shop Asimetri Kopi. The research approach used is a qualitative method supported by data. The sample consisted of 97 respondents who were taken using accidental sampling technique. The types of data used include primary and secondary data. Data collection methods include interviews, observations, literature studies, and questionnaires, with data collection techniques carried out through distributing questionnaires. Instrument testing uses validity tests and reliability tests, then the data is transformed using the Successive Interval Method (MSI). The analysis technique and hypothesis testing used is multiple linear regression analysis, by previously performing classical assumption tests including normality test, multicollinearity test, and heteroscedasticity test. The results showed that simultaneously the variables of product (X1), price (X2), place (X3), promotion (X4), process (X5), people (X6), and physical evidence (X7) had an effect on customer satisfaction because they obtained a Sig value (0.000) > 0.05. The place variable (X3) obtained Sig (0.019) < 0.05, promotion (X4) obtained a Sig value (0.046) < 0.05, process (X5) has a Sig value (0.037) < 0.05, people (X6) have a Sig value (0.048) < 0.05, and physical evidence (X7) has a Sig value (0, 009) < 0.05 has a partial effect on customer satisfaction, while the product variable (X1) obtained a Sig value (0.125) > 0.05, and the price (X2) obtained a Sig value (0.116) > 0.05 has no partial effect on customer satisfaction. Based on the results of multiple linear regression, it can be concluded that of the seven marketing mix variables that affect customer satisfaction is the people variable of 2.332. Keywords: marketing mix, customer satisfaction, coffee shop, asimetri kopi